Effects of peptidyl-prolyl isomerase 1 depletion in animal models of prion diseases. Issue 2 (4th March 2018) - Legname, Giuseppe; Virgilio, Tommaso; Bistaffa, Edoardo; De Luca, Chiara Maria Giulia; Catania, Marcella; Zago, Paola; Isopi, Elisa; Campagnani, Ilaria; Tagliavini, Fabrizio; Giaccone, Giorgio; Moda, Fabio
ABSTRACT: Pin1 is a peptidyl-prolyl isomerase that induces the cis-trans conversion of specific Ser/Thr-Pro peptide bonds in phosphorylated proteins, leading to conformational changes through which Pin1 regulates protein stability and activity. Since down-regulation of Pin1 has been described in several neurodegenerative disorders, including Alzheimer's Disease (AD), Parkinson's Disease (PD) and Huntington's Disease (HD), we investigated its potential role in prion diseases. Animals generated on wild-type (Pin1 +/+ ), hemizygous (Pin1 +/− ) or knock-out (Pin1 −/− ) background for Pin1 were experimentally infected with RML prions. The study indicates that, neither the total depletion nor reduced levels of Pin1 significantly altered the clinical and neuropathological features of the disease.